Menyoal Penentuan Araha Kiblat Makam Kedatuan Selaparang Lombok Timur Menggunakan Istiwa'aini - Putri Rizkika Purnama Sari; Siti Rabi'atul Adawiyah; Muhammad Harfin Zuhdi (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
This research was conducted to investigate the method of determining the Qibla direction used at the Selaparang Kedatuan Tomb, East Lombok, as well as to re-examine the accuracy of the Qibla direction of the tomb. This research is qualitative research that uses a field approach. Research data was collected through observation, interviews, and documentation. Meanwhile, the data analysis process is carried out through data reduction, data presentation, and conclusion. The results of the research show that determining the direction of the Qibla of the Selaparang Kedatuan Tomb in East Lombok uses a method derived from the development of the Istiwa' stick which applies a concept that is identical to the theory of Spherical Trigonometry. Meanwhile, the results of the Qibla direction calibration that was carried out using istiwa'aini showed that there was a deviation in the Qibla direction of the Selaparang Kedatuan Tomb, East Lombok, from the Kaaba of Thus, the direction of the tomb's Qibla is currently inaccurate. This condition occurred .?9.62?48 ?26 because the method for measuring the direction of the Qibla used by its predecessors at that time still had many shortcomings.